Etiology of nocturia response in men with diminished bladder capacity. Issue 1 (12th October 2018) - Epstein, Matthew R.; Monaghan, Thomas; Weiss, Jeffrey P.
Abstract : Aims: To test the hypothesis that patients with nocturia owing to diminished global or nocturnal bladder capacity improve via increased bladder capacity. Methods: This is a retrospective analysis of voiding diaries completed at a VA urology clinic between 2008–2017. Inclusion required patients aged at least 18 years, male, undergoing treatment for nocturia, and having completed at least two 24‐hour voiding diaries ≥1 month apart. Patients were divided into two cohorts: responders (any decline in nocturia) and non‐responders (no change or any increase in nocturia). Patients were further sub‐stratified as having low global bladder capacity (maximum voided volume [MVV] <200 mL) versus low nocturnal bladder capacity (nocturnal maximum voided volume [NMVV] <200 mL and MVV ≥200 mL). Wilcoxon rank‐sum was applied with a Bonferroni correction to test significance. Results: Forty pre‐ and post‐treatment diaries from 27 patients, and 19 pre‐ and post‐treatment diaries from 17 patients were identified as having low global and low nocturnal bladder capacity, respectively. Nocturia responders with low global bladder capacity demonstrated significant decline compared to non‐responders in nocturnal urine volume (NUV) (−140 vs +75, P < 0.01) and nocturnal bladder capacity index (NBCi) (−0.59 vs +0.23, P < 0.01). Patients with low nocturnal bladder capacity similarly demonstrated decreased NUV (−30 vs +160, P = 0.04) and NBCi (−1.4 vs +0.33, P < 0.01). There was no significant change in MVV or NMVV for either group. Conclusions: Treatment directed at lowering nocturnal urine production and enabling patients to consistently void at capacity is a rational strategy to treat nocturia in patients with low bladder capacity.